PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF NHT UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN DENGAN MEDIA POWER POINT PADA SISWA KELAS III SDN NGENGOR MADIUN - Titis Nalawati (Almeera Education, 2022)
Based on observations at SDN Ngengor, it was found that the problems in learning were not varied at SDN Ngengor. Research by applying the NHT cooperative learning model with powerpoint media can improve the quality of science learning for grade III students. This type of research uses classroom action. The research subjects were teachers and third grade students. Techniques for collecting test data, observations, notes and documentation. The results of the first cycle of teacher skills obtained a score of 18. Cycle II obtained a score of 26. Student activity in cycle I obtained a score of 13.6 and a score of 19.4 at the second meeting. Cycle II increased to a score of 24 at the first meeting and a score of 26 at the second meeting. the classical cycle I was 67%, the second cycle increased to 87%. The conclusion is that through the application of the NHT cooperative model with powerpoint media, it can improve teacher skills, student activities, and student learning outcomes for Class III students. Suggestions should use innovative models and varied media in learning.